The wrong Spirochaete? Acute kidney injury in a returning traveller with syphilis – a case report - Cook, Hannah; Gompels, Mark (BMC infectious diseases, 2020)
Background Syphilis has seen an increased incidence in recent years and can have serious and irreversible consequences if left un-diagnosed and untreated. This case report describes a presentation of syphilis and acute kidney injury – a scenario sparsely described in existing literature. Case presentation This 43-year old Man who has Sex with Men (MSM) presented to the emergency department with a 3-week history of vomiting and headaches, progressing to include pyrexia. These symptoms started following his return from a 2-week cruise in Central America throughout which he had been well. He had a background of well-controlled human immunodeficiency virus (HIV). On admission he had an Acute Kidney Injury (AKI) stage 3, without hydronephrosis, presumed to be pre-renal. Leptospirosis, the main differential, was negative serologically. ‘Pyrexia of unknown origin’ testing was performed, and cefuroxime commenced. Later in the admission, syphilis testing indicated an acute infection and he completed a full treatment course of benzylpenicillin. This, alongside intravenous fluids, resulted in symptom and renal resolution in 9 days and restoration of renal function. Conclusions Renal complications in syphilis are rare, furthermore the majority of those documented occur in latent syphilis and are irreversible. There are limited numbers of other documented cases of AKI in acute syphilis, which like the gentleman in this case were reversible and did not lead to permanent kidney damage. This case adds to the knowledge base of AKI in initial presentation of syphilis. It also demonstrates not only the importance of taking a sexual history in patients with new infective symptoms but that testing for syphilis in at-risk groups regardless of history should be performed given its rising incidence. These considerations by physicians can lead to prompt diagnosis and management of syphilis and improve patient care and long-term outcomes.